Creative Reasoning in Mathematics Problem Solving: A Systematic Literature Review of Descriptive Content Analysis Using Bibliometrics - Buaddin Hasan; Lukman Jakfar Shodiq (Universitas Pendidikan Ganesha, 2025)
Research on creative reasoning in mathematical problem-solving continues to grow significantly, as evidenced by global trends and the large number of publications identified through bibliometric analysis and the PRISMA systematic review. This study aims to analyze the trends in further research on creative reasoning and to examine aspects of creative reasoning used in mathematical problem-solving. This study employed a library research design using both bibliometric and descriptive approaches. Scientific publications related to creative reasoning served as the data sources. Data were collected through database searches using the string